REPRESENTASI GENDER DALAM IKLAN CETAK MINUMAN DIET COKE DI PRANCIS - Karlina Dewi, Riza; Miranda, Airin (Universitas Hasanuddin, 2024)
This research aims to explain the gender representation displayed in the Diet Coke drink advertisement which collaborates with the famous French fashion designer, Jean-Paul Gaultier. The method used in this research is qualitative. The focus of this research is to show the gender representation of two female characters in the Coca-Cola advertisement which shows the two women wearing women's clothes but on the other hand, their faces are covered by the image of Jean-Paul Gaultier, who is a man. Gender representation is shown in these two advertisements through the advertising models, the clothes they wear, poses, dominant colors in the advertisement, packaging design, and typography. Through the representation of colors, poses, clothes, etc., it can be seen that there is a gender representation that is not follow the gender rules that apply in society.